High-conductivity adhesive film, preparation method and application of high-conductivity adhesive film to antenna module
By using a highly conductive adhesive film of modified flake silver powder and carbon nanotubes in the antenna module, combined with the toughening modification of carboxyl-terminated polyurethane, the problem of insufficient conductivity and strength in the miniaturized antenna module is solved, achieving Lower volume resistivity and higher shear strength.
Patent Information
- Application Number
- CN202411401937.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
In the development of 5G technology and millimeter wave applications, the design requirements of antenna modules are becoming increasingly small and refined, resulting in a reduction in the reserved bond area, and complex designs require better grounding and shielding solutions, but existing conductive The glue performance is not sufficient to meet these needs.
By adding the modified sliced silver powder and carbon nanoplasses to the epoxy resin, prepare a high-conductive film, use the carboxyl seal polyurethane for toughness and modification, and firmly adsorb the carbon nanotubes through the action of π-π. Conductive performance and strength.
It achieves lower volume resistivity and higher shear strength of the conductive adhesive film, meeting the requirements for conductive performance and strength in antenna modules.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive adhesives, and in particular to a highly conductive adhesive film, a preparation method and application in an antenna module. Background Art
[0002] Conductive adhesive is an adhesive that has conductive properties after drying or curing. Its main function is to connect multiple conductive materials together to form a conductive path between the connected materials. At present, conductive adhesive has become an indispensable new material in the electronics industry. There are many types of conductive adhesives. The currently disclosed conductive adhesive systems are mainly concentrated in epoxy systems, which are usually divided into two categories: general conductive adhesives and special conductive adhesives. General conductive adhesives only have certain requirements for the conductive properties and bonding strength of conductive adhesives. In addition to certain requirements for conductive properties and bonding strength, special conductive adhesives also have certain special requirements, such as high and low temperature resistance, fast curing, anisotropy, transparency, etc. According to the type of conductive material added to the conductive adhesive, it can be subdivided into silver-based conductive adhesives, gold-based conductive adhesives, copper-based conductive adhesives, and carbon-based conductive adhesives, among which silver-based conductive adhesives are the most widely used.
[0003] The continuous development of 5G technology has led to a significant increase in 5G frequency. In the millimeter wave range, the size of antennas has shrunk dramatically. The design of electronic equipment is also becoming more and more miniaturized and refined. The arrangement of internal components of the equipment is becoming more and more precise, and the reserved bonding area is gradually decreasing. Complex designs require better grounding and shielding solutions. Therefore, it is necessary to develop a new generation of conductive adhesive series solutions. Summary of the invention
[0004] The object of the present invention is to provide a highly conductive adhesive film, a preparation method and application in an antenna module to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a highly conductive adhesive film, a preparation method and an application in an antenna module, comprising the following steps:
[0006] Step 1:
[0007] Adding modified flaky silver powder to epoxy resin and stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane and stirring to obtain component B; adding component B to component A to obtain a mixed rubber material;
[0008] Step 2:
[0009] By weight, 2 to 4 parts of active diluent, 4 to 6 parts of triethylenetetramine curing agent, 10 to 15 parts of anhydrous ethanol, 3 to 5 parts of nano silicon dioxide, 0 to 10 parts of nickel powder and 0 to 10 parts of copper powder are added to 100 parts of mixed adhesive to obtain a highly conductive adhesive.
[0010] Furthermore, in step 1, in component A, modified flaky silver powder and epoxy resin are mixed in a weight ratio of (3-4):1; in component B, carbon nanotubes and carboxyl-terminated polyurethane are mixed in a weight ratio of 1:(1-1.2).
[0011] Furthermore, in step 1, the method for preparing the modified flaky silver powder comprises the following steps:
[0012] a. Mix glutaric acid and anhydrous ethanol and stir to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 20 to 25%;
[0013] b. Add flaky silver powder to the surface activation treatment solution, ultrasonically treat for 10 to 20 minutes, collect the solid by filtration and rinse with anhydrous ethanol, and then place it under vacuum at 40 to 50°C to obtain modified flaky silver powder.
[0014] Furthermore, in step 1, the method for preparing the carboxyl-terminated polyurethane comprises the following steps:
[0015] S1: Potassium hydroxide, potassium iodide and 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed, the catalyst is added, and the mixture is refluxed for 45 to 50 hours. After cooling, dichloromethane is added, the insoluble impurities are removed by filtration, and the filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole;
[0016] S2: epoxy carbazole and 2,2-bis(hydroxymethyl) propionic acid are dispersed in deionized water, and reacted at 80-90° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole;
[0017] S3: Mix 280-330 parts of isophorone diisocyanate and 100 parts of polyethylene glycol 2000 by weight, use dibutyltin dilaurate as a catalyst, and react for 2-3 hours at 30-40°C and nitrogen atmosphere; add 46-68 parts of bis(hydroxymethyl)grafted carbazole and continue to react for 1-2 hours to obtain an isocyanate-terminated polyurethane prepolymer; heat to 40-50°C, add 1,2,4-benzenetricarboxylic anhydride, continue to heat to 90-100°C and react for 2-3 hours to obtain a carboxyl-terminated polyurethane.
[0018] Furthermore, in S1, the contents of the components in the catalyst are, by weight, 100 parts of potassium hydroxide, 2 to 3 parts of potassium iodide, 7 to 8 parts of 18-crown-6; N-hydroxyethylcarbazole, and epichlorohydrin are mixed in a molar ratio of 1:(3 to 4).
[0019] Furthermore, in S2, epoxycarbazole and 2,2-bis(hydroxymethyl)propionic acid react at a molar ratio of epoxy group to carboxyl group of 1:1.
[0020] Furthermore, in S3, in the polyurethane prepolymer, the amount of each component, by weight, is 280-330 parts of isophorone diisocyanate, 100 parts of polyethylene glycol 2000, and 46-68 parts of bis(hydroxymethyl)grafted carbazole.
[0021] Further, in S3, 1,2,4-benzenetricarboxylic anhydride is added to the polyurethane prepolymer at a molar ratio of 1,2,4-benzenetricarboxylic anhydride to isocyanate group of 1:1.
[0022] Furthermore, the application method of the highly conductive adhesive film on the antenna module is: at 80-100°C, 3-5kgf / cm 2 The highly conductive adhesive film is rolled and attached to the surface of the antenna substrate at a speed of 1 to 3 m / min, and the antenna substrate with the highly conductive adhesive film attached is assembled into a mold to obtain an antenna module.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention adds flaky silver powder to epoxy resin to prepare a highly conductive adhesive film for antenna modules. Generally, spherical silver powder is often used in conductive adhesive films, but the spherical silver powders form a conductive path through point-to-point contact, while the flaky silver powders in the present application are not only in point-to-point contact, but also in surface-to-surface contact, which can give the conductive adhesive film a lower volume resistivity. The present invention uses glutaric acid to modify the flaky silver powder, thereby improving the connection strength between it and the epoxy resin and improving the conductive properties of the conductive adhesive film.
[0024] In order to improve the performance of the conductive adhesive film, the present invention uses epoxy resin and modified flaky silver powder as component A, and selects polyurethane as component B to toughen and modify it. After polyurethane and epoxy resin are directly blended and cured, a three-dimensional interpenetrating polymer network structure can be formed, and the stress generated when subjected to external force can be better transmitted and dispersed inside the material, thereby enhancing strength and toughness. However, the curing conditions of epoxy resin and polyurethane are different, and the two have the problem of poor compatibility. Therefore, the present invention uses 1,2,4-benzenetricarboxylic anhydride to end-cap the polyurethane prepolymer, and uses the carboxyl group to react with the epoxy group, so that the two are chemically cross-linked to improve the modification effect. The researchers found that the second phase produced by the sea-island effect in the epoxy resin used for toughening of the carboxyl-terminated polyurethane plays a role in increasing the shear strength of the conductive adhesive, but the presence of the sea-island effect also hinders the contact between the flaky silver powder in the epoxy resin, affecting the conductive performance. The researchers continued to add carbon nanotubes to the carboxyl-terminated polyurethane of component B and blended it with component A, but the conductive properties of the film were still poor. The possible reasons were analyzed as follows: during blending, the carbon nanotubes in component B will be randomly dispersed into component A, resulting in a decrease in the carbon nanotube content in component B and poor conductive properties. For this reason, the present invention introduces carbazole groups into the carboxyl-terminated polyurethane in component B, and utilizes the strong π-π interaction between the carbazole groups and the carbon nanotubes to firmly adsorb the carbon nanotubes in the carboxyl-terminated polyurethane, thereby effectively avoiding the occurrence of the above-mentioned problems. In addition, a small amount of nano-silicon dioxide, copper powder, and nickel powder are added to the present invention as reinforcing materials; among them, nano-silicon dioxide improves the wear resistance of the conductive film, and copper powder, nickel powder, etc. also have good conductive properties. Adding nano-silicon dioxide, copper powder, and nickel powder to the conductive film can not only improve the strength of the conductive film, but also ensure that it has good conductive properties. The conductive film prepared by the present invention has a large shear strength and a volume resistivity of less than 5×10 -4 Ω / cm, strong conductivity. DETAILED DESCRIPTION
[0025] Materials and sources used in the present invention: bisphenol A epoxy resin E-51 comes from Henan Chiao Trading; flaky nano silver powder (model XFJ45), nano silicon dioxide (model XFI03), and carbon nanotubes (model XFM31) are all from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; active diluent (model LS-622) is from Hubei Green Home Materials Technology Co., Ltd.; copper powder (Cu>99.85%, spherical) and nickel powder (Ni>99.85%, spherical) are all from Hunan Huabang Powder Material Co., Ltd.
[0026] Embodiment 1: A method for preparing a highly conductive adhesive film, comprising the following steps:
[0027] Step 1:
[0028] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0029] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 10 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 40° C. to obtain modified flaky silver powder;
[0030] Step 2:
[0031] S21: 100 g potassium hydroxide, 2 g potassium iodide, and 8 g 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed in a molar ratio of 1:4, the catalyst is added, and the mixture is refluxed for 45 h. After cooling, dichloromethane is added, and insoluble impurities are removed by filtration. The filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole;
[0032] S22: epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are dispersed in deionized water, and reacted at 80° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole; wherein the epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are reacted at a molar ratio of epoxy group to carboxyl group of 1:1;
[0033] S23: 300 g of isophorone diisocyanate and 100 g of polyethylene glycol 2000 were mixed, dibutyltin dilaurate was used as a catalyst, and the mixture was reacted at 30° C. under a nitrogen atmosphere for 2 h; 52 g of bis(hydroxymethyl) grafted carbazole was added and the reaction was continued for 1 h to obtain an isocyanate-terminated polyurethane prepolymer; the temperature was raised to 40° C., 1,2,4-benzenetricarboxylic anhydride was added at a molar ratio of 1:1 to isocyanate group, and the temperature was continued to be raised to 90° C. and the reaction was carried out for 2 h to obtain a carboxyl-terminated polyurethane;
[0034] Step 3:
[0035] S31: adding modified flaky silver powder to epoxy resin at a weight ratio of 3:1, stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane at a weight ratio of 1:1, stirring to obtain component B; adding component B to component A to obtain a mixed rubber; the content of each component in the mixed rubber, by weight percentage, is 80% component A and 20% component B;
[0036] S32: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film and dry it at 60°C to form a highly conductive adhesive film.
[0037] Embodiment 2: A method for preparing a highly conductive adhesive film, comprising the following steps:
[0038] Step 1:
[0039] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0040] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 15 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 45° C. to obtain modified flaky silver powder;
[0041] Step 2:
[0042] S21: 100 g potassium hydroxide, 2 g potassium iodide, and 8 g 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed in a molar ratio of 1:4, the catalyst is added, and the mixture is refluxed for 48 h. After cooling, dichloromethane is added, and insoluble impurities are removed by filtration. The filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole;
[0043] S22: epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are dispersed in deionized water, and reacted at 85° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole; wherein the epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are reacted at a molar ratio of epoxy group to carboxyl group of 1:1;
[0044] S23: 300 g of isophorone diisocyanate and 100 g of polyethylene glycol 2000 were mixed, dibutyltin dilaurate was used as a catalyst, and the mixture was reacted at 35° C. under a nitrogen atmosphere for 2.5 h; 52 g of bis(hydroxymethyl) grafted carbazole was added and the reaction was continued for 1.5 h to obtain an isocyanate-terminated polyurethane prepolymer; the temperature was raised to 45° C., 1,2,4-benzenetricarboxylic anhydride was added at a molar ratio of 1:1 to isocyanate group, and the temperature was continued to be raised to 95° C. and the reaction was carried out for 2.5 h to obtain a carboxyl-terminated polyurethane;
[0045] Step 3:
[0046] S31: adding modified flaky silver powder to epoxy resin at a weight ratio of 3.5:1, stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane at a weight ratio of 1:1, stirring to obtain component B; adding component B to component A to obtain a mixed rubber; the content of each component in the mixed rubber, by weight percentage, is 80% component A and 20% component B;
[0047] S32: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder, and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film, and dry at 65°C to form a highly conductive adhesive film.
[0048] Embodiment 3: A method for preparing a highly conductive adhesive film, comprising the following steps:
[0049] Step 1:
[0050] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0051] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 20 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 50° C. to obtain modified flaky silver powder;
[0052] Step 2:
[0053] S21: 100 g potassium hydroxide, 2 g potassium iodide, and 8 g 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed in a molar ratio of 1:4, the catalyst is added, and the mixture is refluxed for 50 h. After cooling, dichloromethane is added, and insoluble impurities are removed by filtration. The filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole;
[0054] S22: epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are dispersed in deionized water, and reacted at 90° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole; wherein the epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are reacted at a molar ratio of epoxy group to carboxyl group of 1:1;
[0055] S23: 300 g of isophorone diisocyanate and 100 g of polyethylene glycol 2000 were mixed, dibutyltin dilaurate was used as a catalyst, and the mixture was reacted at 40° C. under a nitrogen atmosphere for 3 h; 52 g of bis(hydroxymethyl) grafted carbazole was added and the reaction was continued for 2 h to obtain an isocyanate-terminated polyurethane prepolymer; the temperature was raised to 50° C., 1,2,4-benzenetricarboxylic anhydride was added at a molar ratio of 1:1 to isocyanate group, and the temperature was continued to be raised to 100° C. and the mixture was reacted for 3 h to obtain a carboxyl-terminated polyurethane;
[0056] Step 3:
[0057] S31: adding modified flaky silver powder to epoxy resin at a weight ratio of 4:1, stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane at a weight ratio of 1:1, stirring to obtain component B; adding component B to component A to obtain a mixed rubber; the content of each component in the mixed rubber, by weight percentage, is 80% component A and 20% component B;
[0058] S32: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film and dry it at 70°C to form a highly conductive adhesive film.
[0059] Comparative Example 1: Component A was used to replace the mixed rubber material, and the other parameters were the same as those in Example 1.
[0060] Step 1:
[0061] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0062] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 10 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 40° C. to obtain modified flaky silver powder;
[0063] Step 2:
[0064] S21: adding the modified flaky silver powder to the epoxy resin at a weight ratio of 3:1 to obtain a mixed adhesive;
[0065] S22: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder, and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film, and dry at 60°C to form a highly conductive adhesive film.
[0066] Comparative Example 2: Component B was replaced by carboxyl-terminated polyurethane, and the other parameters were the same as those in Example 2.
[0067] Step 1:
[0068] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0069] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 15 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 45° C. to obtain modified flaky silver powder;
[0070] Step 2:
[0071] S21: 100 g potassium hydroxide, 2 g potassium iodide, and 8 g 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed in a molar ratio of 1:4, the catalyst is added, and the mixture is refluxed for 48 h. After cooling, dichloromethane is added, and insoluble impurities are removed by filtration. The filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole;
[0072] S22: epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are dispersed in deionized water, and reacted at 85° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole; wherein the epoxy carbazole and 2,2-bis(hydroxymethyl)propionic acid are reacted at a molar ratio of epoxy group to carboxyl group of 1:1;
[0073] S23: 300 g of isophorone diisocyanate and 100 g of polyethylene glycol 2000 were mixed, dibutyltin dilaurate was used as a catalyst, and the mixture was reacted at 35° C. under a nitrogen atmosphere for 2.5 h; 52 g of bis(hydroxymethyl) grafted carbazole was added and the reaction was continued for 1.5 h to obtain an isocyanate-terminated polyurethane prepolymer; the temperature was raised to 45° C., 1,2,4-benzenetricarboxylic anhydride was added at a molar ratio of 1:1 to isocyanate group, and the temperature was continued to be raised to 95° C. and the reaction was carried out for 2.5 h to obtain a carboxyl-terminated polyurethane;
[0074] Step 3:
[0075] S31: adding modified flaky silver powder to epoxy resin at a weight ratio of 3.5:1, stirring to obtain component A; adding carboxyl-terminated polyurethane to component A to obtain a mixed rubber; the content of each component in the mixed rubber, by weight percentage, is 80% component A and 20% carboxyl-terminated polyurethane;
[0076] S32: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder, and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film, and dry at 65°C to form a highly conductive adhesive film.
[0077] Comparative Example 3: Carboxyl-terminated polyurethane was prepared without using bis(hydroxymethyl) grafted carbazole, and the other parameters were the same as those in Example 3.
[0078] Step 1:
[0079] S11: mixing glutaric acid and anhydrous ethanol, and stirring to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 25%;
[0080] S12: adding flaky silver powder to the surface activation treatment solution, ultrasonically treating for 20 minutes, filtering and collecting the solid, rinsing with anhydrous ethanol, and vacuum drying at 50° C. to obtain modified flaky silver powder;
[0081] Step 2:
[0082] 300 g of isophorone diisocyanate and 100 g of polyethylene glycol 2000 were mixed, dibutyltin dilaurate was used as a catalyst, and the mixture was reacted at 40° C. under a nitrogen atmosphere for 3 h; 29 g of 2,2-bis(hydroxymethyl)propionic acid was added and the reaction was continued for 2 h to obtain an isocyanate-terminated polyurethane prepolymer; the temperature was raised to 50° C., 1,2,4-benzenetricarboxylic anhydride was added at a molar ratio of 1:1 to isocyanate group, the temperature was continued to be raised to 100° C. and the mixture was reacted for 3 h to obtain a carboxyl-terminated polyurethane;
[0083] Step 3:
[0084] S31: adding modified flaky silver powder to epoxy resin at a weight ratio of 4:1, stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane at a weight ratio of 1:1, stirring to obtain component B; adding component B to component A to obtain a mixed rubber; the content of each component in the mixed rubber, by weight percentage, is 80% component A and 20% component B;
[0085] S32: Add 2g of active diluent, 4g of triethylenetetramine curing agent, 12g of anhydrous ethanol, 4g of nano-silicon dioxide, 10g of nickel powder and 10g of copper powder to 100g of the mixed adhesive to obtain a highly conductive adhesive; apply the highly conductive adhesive on a release film and dry it at 70°C to form a highly conductive adhesive film.
[0086] Experiment: Prepare samples according to the schemes in Examples 1 to 3 and Comparative Examples 1 to 3 for performance testing. Among them, volume resistivity test: refer to method 5011 in standard GJB548A-1996, apply high conductive adhesive on a standard glass slide with a size of 2.54cm×7.62cm, and form a conductive adhesive film sample after drying; use RTS-8 four-point probe to test the resistance of the sample, measure 5 times for each group of samples, and record the average value. Shear strength test: refer to standard GB7124-86 (A1 / A1 overlap), the overlap specimen is LY12CZ aluminum alloy with a length of (100±0.2) mm, a width of (25±0.2) mm, and a thickness of (2±0.1) mm. Use an electronic universal testing machine for testing, the tensile speed is 5 mm / min, and 5 samples are made in each group to take the average value. The experimental results are shown in Table 1.
[0087] Table 1. Test results of various properties of conductive film
[0088] project <![CDATA[Volume resistivity (10 -4 Ω / cm)]]> Shear strength(MPa) Example 1 4.82 13.8 Example 2 4.64 14.3 Example 3 4.25 14.7 Comparative Example 1 4.15 10.2 Comparative Example 2 19.36 13.4 Comparative Example 3 8.47 12.1
[0089] Conclusion: The data in Examples 1 to 3 show that the conductive adhesive prepared by the present invention has good conductivity and high shear strength. The data in Example 1 and Comparative Example 1 show that the addition of carboxyl-terminated polyurethane effectively improves the shear strength of the conductive adhesive film; the data in Example 2 and Comparative Example 2 show that when only carboxyl-terminated polyurethane is added, the second phase produced by the carboxyl-terminated polyurethane in the epoxy resin system through the sea-island effect plays a role in increasing the shear strength of the conductive adhesive, but hinders the contact between the silver powder fillers, so the conductive performance decreases; the data in Example 3 and Comparative Example 3 show that after using bis (hydroxymethyl) grafted carbazole to prepare carboxyl-terminated polyurethane, both the conductive performance and the shear strength are improved.
[0090] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0091] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly conductive adhesive film, characterized in that: The following steps are involved: Step 1: Adding modified flaky silver powder to epoxy resin and stirring to obtain component A; adding carbon nanotubes to carboxyl-terminated polyurethane and stirring to obtain component B; adding component B to component A to obtain a mixed rubber material; Step 2: To 100 parts of the mixed adhesive, 2 to 4 parts of active diluent, 4 to 6 parts of triethylenetetramine curing agent, 10 to 15 parts of anhydrous ethanol, 3 to 5 parts of nano silicon dioxide, 0 to 10 parts of nickel powder and 0 to 10 parts of copper powder are added by weight to obtain a highly conductive adhesive; the highly conductive adhesive is coated on a release film and dried at 60 to 70° C. to obtain a highly conductive adhesive film.
2. The method for preparing a highly conductive adhesive film according to claim 1, characterized in that: In step 1, in component A, modified flaky silver powder and epoxy resin are mixed in a weight ratio of (3-4):1; in component B, carbon nanotubes and carboxyl-terminated polyurethane are mixed in a weight ratio of 1:(1-1.2).
3. The method for preparing a highly conductive adhesive film according to claim 1, characterized in that: In step 1, the method for preparing the modified flaky silver powder comprises the following steps: a. Mix glutaric acid and anhydrous ethanol and stir to obtain a surface activation treatment solution, wherein the mass concentration of glutaric acid in the surface activation treatment solution is 20 to 25%; b. Add flaky silver powder to the surface activation treatment solution, ultrasonically treat for 10 to 20 minutes, collect the solid by filtration and rinse with anhydrous ethanol, and then place it under vacuum at 40 to 50°C to obtain modified flaky silver powder.
4. The method for preparing a highly conductive adhesive film according to claim 1, characterized in that: In step 1, the method for preparing the carboxyl-terminated polyurethane comprises the following steps: S1: Potassium hydroxide, potassium iodide and 18-crown-6 are mixed to obtain a catalyst; N-hydroxyethyl carbazole and epichlorohydrin are mixed, the catalyst is added, and the mixture is refluxed for 45 to 50 hours. After cooling, dichloromethane is added, the insoluble impurities are removed by filtration, and the filtrate is subjected to rotary evaporation to remove dichloromethane to obtain epoxy-grafted carbazole; S2: epoxy carbazole and 2,2-bis(hydroxymethyl) propionic acid are dispersed in deionized water, and reacted at 80-90° C. using benzyltriethylammonium chloride as a catalyst to obtain bis(hydroxymethyl) grafted carbazole; S3: Mix 280-330 parts of isophorone diisocyanate and 100 parts of polyethylene glycol 2000 by weight, use dibutyltin dilaurate as a catalyst, and react for 2-3 hours at 30-40°C and nitrogen atmosphere; add 46-68 parts of bis(hydroxymethyl)grafted carbazole and continue to react for 1-2 hours to obtain an isocyanate-terminated polyurethane prepolymer; heat to 40-50°C, add 1,2,4-benzenetricarboxylic anhydride, continue to heat to 90-100°C and react for 2-3 hours to obtain a carboxyl-terminated polyurethane.
5. The method for preparing a highly conductive adhesive film according to claim 3, characterized in that: In S1, the contents of the components in the catalyst are, by weight, 100 parts of potassium hydroxide, 2 to 3 parts of potassium iodide, 7 to 8 parts of 18-crown-6; N-hydroxyethylcarbazole, and epichlorohydrin are mixed in a molar ratio of 1:(3 to 4).
6. The method for preparing a highly conductive adhesive film according to claim 3, characterized in that: In S2, epoxycarbazole and 2,2-bis(hydroxymethyl)propionic acid react in a molar ratio of epoxy group to carboxyl group of 1:
1.
7. The method for preparing a highly conductive adhesive film according to claim 3, characterized in that: In S3, in the polyurethane prepolymer, the amount of each component, by weight, is 280-330 parts of isophorone diisocyanate, 100 parts of polyethylene glycol 2000, and 46-68 parts of bis(hydroxymethyl)grafted carbazole.
8. The method for preparing a highly conductive adhesive film according to claim 3, characterized in that: In S3, 1,2,4-benzenetricarboxylic anhydride is added to the polyurethane prepolymer at a molar ratio of 1,2,4-benzenetricarboxylic anhydride to isocyanate group of 1:
1. 9 . The highly conductive adhesive film prepared by the preparation method according to claim 1 .
10. An application of the highly conductive adhesive film as claimed in claim 9 on an antenna module, characterized in that: At 80~100℃, 3~5kgf / cm 2 The highly conductive adhesive film is rolled and attached to the surface of the antenna substrate at a speed of 1 to 3 m / min, and the antenna substrate with the highly conductive adhesive film attached is assembled into a mold to obtain an antenna module.
Citation Information
Patent Citations
A polyurethane-epoxy resin hybrid electrically conductive adhesive, a preparing method thereof and an electrically conductive film
CN105838311A
Nano-silver sintered conductive adhesive for microelectronic packaging and preparation method of nano-silver sintered conductive adhesive
CN114276766A
High-conductivity conductive adhesive as well as preparation method and application thereof
CN115386327A
Conductive adhesive, conductive adhesive preparation method, conductive adhesive film, and conductive adhesive film preparation method and application thereof
CN117165237A
Conductive silver adhesive based on modified silver powder and preparation method thereof
CN117487496A